The Contribution of African Women to Economic Growth and Development : Historical Perspectives and Policy Implications, Part I, The Pre-colonial and Colonial Periods - Akyeampong, Emmanuel; Fofack, Hippolyte (World Bank, Washington, DC, 2012)
Bringing together history and economics, this paper presents a historical and processual understanding of women's economic marginalization in Sub-Saharan Africa from the pre-colonial period to the end of colonial rule. It is not that women have not been economically active or productive; it is rather that they have often not been able to claim the proceeds of their labor or have it formally accounted for. The paper focuses on the pre-colonial and colonial periods and outlines three major arguments. First, it discusses the historical processes through which the labor of women was increasingly appropriated even in kinship structures in pre-colonial Africa, utilizing the concepts of "rights in persons" and "wealth in people." Reviewing the processes of production and reproduction, it explains why most slaves in pre-colonial Africa were women and discusses how slavery and slave trade intensified the exploitation of women. Second, it analyzes how the cultivation of cash crops and European missionary constructions of the individual, marriage, and family from the early decades of the 19th century sequestered female labor and made it invisible in the realm of domestic production. Third, it discusses how colonial policies from the late 19th century reinforced the "capture" of female labor and the codification of patriarchy through the nature and operation of the colonial economy and the instrumentality of customary law. The sequel to this paper focuses on the post-colonial period. It examines the continuing relevance and impact of the historical processes this paper discusses on post-colonial economies, and suggests some policy implications.